Partisipasi Guru Dalam Pelaksanaan Bimbingan dan Konseling di Lembaga Pendidikan Islam: Studi Kasus di MA Ronggowarsito Ponorogo - Kayyis Fithri Ajhuri; Hafidh 'Aziz (Jurnal Pendidikan Madrasah, 2021)
The education concept in Islamic perspective does not stop at the task of transforming knowledge, but is involved in the process of guidance and character building. The purpose of this study is to analyze teacher participation in the implementation of Guidance and Counseling in Islamic Education Institutions. This research is a case study with a single case model, namely the case at MA Ronggowarsito Tegalsari Jetis Ponorogo. Through observation, in-depth semi-structured interviews and data documentation were collected, then analyzed using the interactive model of Miles and Huberman. The results showed, first, the teachers at MA Ronggowarsito have a commitment to help children's difficulties, especially in the academic field. The form of the teacher's willingness includes, willingness to provide guidance and enrichment. Personal consultation, even changes in learning models according to the conditions and characteristics of students. In the non-academic field, the teacher's readiness takes the form of a willingness to guide extra and co-curricular activities. Second, related to the main tasks and functions of guidance and counseling teachers, teacher participation in the implementation of the BK program is supportive and preventive at the class level. The coordination that is carried out also tends to be unstructured and incidental